Experience in Strengthening Prefabricated Reinforced Concrete Floor Systems During the Rehabilitation of Industrial Buildings - Marchenko, Valentyn; Fedorov, Dmytro (Academic journal Industrial Machine Building Civil Engineering, 2025)
The article presents practical experience in combined reinforcing of precast reinforced-concrete beams and hollow-core floor panels during rehabilitation of an industrial building at the Chornomorsk Oil and Fat Plant. The initial technical condition of the structures and the results of the instrumental inspection have been described. The existing structure, consisting of long-span beams (up to 12 m) and hollow-core slabs (9 m spans), had suffered physical deterioration, exhibited excessive deflections, and required increased load-bearing capacity for design loads of 10–12 kPa. A proposed constructive-technological system combines: an external cage-truss rigid steel longitudinal reinforcement, increasing the cross-section by reinforced cast-in-place concrete topping, and creation of a monolithic slabs-beams joints. The design of mounting plates and cage-truss to beams joints using chemical anchors is detailed, it includes CBFEM analyses using IDEA StatiCa that demonstrate sufficient capacity and acceptable transfer of forces to the concrete. The procedure for topping the slab is given, including placement of reinforcement cages into the hollow cores, mesh reinforcement across the slab, and staged concreting. Advantages of the combined approach for increasing stiffness and load-bearing capacity and measures to limit local effects on existing sections are analyzed. Implementation results confirm the effectiveness of the proposed solution for restoration and enhancement of operational performance of large-span reinforced-concrete structures in industrial buildings.